Isotope Effect in the Vibrational Predissociation of van der Waals Molecules: Complexes of Glyoxal With H2 and D2. Issue 1 (1982) - Beswick, J. A.; Halberstadt, N.; Jouvet, C.; Soep, B.
Abstract : In this work photodissociation studies of glyoxal-H2 (D2 ) molecules have been conducted in order to analyze the effect of the mass in the vibrational predissociation of van der Waals complexes. The glyoxal-H2 (D2 ) molecules have been formed in a supersonic expansion and photodissociated by means of a tunable dye laser. The final state of the glyoxal fragments has been determined by the analysis of the fluorescence spectrum. A significant isotope effect on the branching ratios for predissociation has been found. An interpretation in terms of a distorted wave diabatic treatment is presented.